Adsorbability Enhancement of Macroporous Resin by Dielectric Barrier Discharge Plasma Treatment to Phenol in Water. (1st November 2016) - Tang, Shoufeng; Yuan, Deling; He, Jun
Abstract : In order to enhance the adsorption efficiency and economize the use of macroporous resin, we have treated it with the dielectric barrier discharge (DBD) plasma to improve its adsorbing capacity for phenol. The effects of operation conditions, for instance, applied voltage, treated time, and air flow rate on resin, were investigated by adsorption kinetics and isotherms. Results showed that the adsorption data were in good agreement with the pseudo-second-order and Freundlich equation. Experimental results showed that the modified resin was 156.5 mg/g and 39.2% higher than the untreated sample, when the modified conditions were conducted for discharge voltage 20 kV, treatment time 45 min, and air flow rate 1.2 L/min. The resin was characterized by FTIR and nitrogen adsorption isotherms before and after the DBD processes. It was found that the reason for the enhancement of resin adsorbability was attributed to the DBD plasma changing the surface physical and chemical structure.